Towards developing a test of global motion for use with Paralympic athletes - Roberts, J. W.; Thompson, B.; Leat, S. J.; Dalton, K. (Scientific Reports, 2020)
The Paralympic classification system for visual impairment only assesses static visual acuity and static visual field despite many Paralympic sports being dynamic in nature. As a first step towards determining whether motion perception tests should be used in Paralympic classification, we assessed whether motion coherence thresholds could be measured when visual acuity or visual fields were impaired at levels consistent with the current Paralympic classification criteria. Visual acuity and visual field impairments corresponding to Paralympic classification criteria were simulated in normally sighted individuals and motion coherence thresholds were measured. Mild-to-moderate visual acuity impairments had no effect on motion coherence thresholds. The most severe Paralympic class of acuity impairment (=2.6 logMAR) significantly elevated thresholds. A trend towards superior motion coherence thresholds in the peripheral visual field compared to the central visual field was also present. Global motion perception appears to be measurable under simulated visual impairments that are consistent with the Paralympic classification. Poorer global motion perception was found for visual acuities >2.6 logMAR and visual fields <10° in diameter. Further research is needed to investigate the relationship between global motion perception and sports performance in athletes with real visual impairment.